Analysis Of The Application Of Alkaline Methods Of Influence On The Bottom Of The Well - Turdiev Farid Razzoq òg'li; Abdirazakov Akmal Ibrahimovich; Haydarov Bahodir Husniddin òg'li (Genius Journals, 2023)
This article provides information on general methods for studying the injection of various surfactants into oil reservoirs.
Keywords: Formation; influence; wells; deposits